Review of subterranean Quedius, with description of the first hypogean species from the Russian Far East (Coleoptera: Staphylinidae: Staphylinini) - Solodovnikov, Alexey; Hansen, Aslak Kappel (Zootaxa, 2016)
Hypogean species of Quedius, one of the largest North Hemisphere beetle genera, are reviewed in connection with the discovery of a new peculiar, brachypterous and microphtalmous species from the subgenus Microsaurus in the talus-based microhabitats of the Russian Far East. Morphology of that species here described as Quedius roma sp. n. suggests its affinity with the przewalskii-group from China and Nepal. Affinity of Q. roma to the abnormalis-group, a geographically more proximate and species-rich and presumably non-monophyletic assemblage of hypogean species from Japan and Taiwan, or to any other Holarctic Microsaurus is not supported morphologically. Two hypogean species from Europe, Q. bernhaueri Rambousek, 1915 and Q. doderoi Gridelli, 1922, are transferred from the subgenus Microsaurus to the subgenus Raphirus. The name Tenebrobius Rambousek, 1915, a subgenus where Q. bernhaueri was originally described, becomes a junior synonym of Raphirus Stephens, 1829.